Regional Agreements and Trade in Services - Mattoo, Aaditya, 1961- 1961- (The World Bank, 2002)
Every major regional trade agreement now has a services dimension. Is trade in services so different that there is need to modify the conclusions on preferential agreements pertaining to goods reached so far? Mattoo and Fink first examine the implications of unilateral policy choices in a particular services market. They then explore the economics of international cooperation and identify the circumstances in which a country is more likely to benefit from cooperation in a regional rather than multilateral forum. This paper--a product of Trade, Development Research Group--is part of a larger effort in the group to assess the implications of liberalizing trade in services. The authors may be contacted at amattoo@worldbank.org or cfink@worldbank.org